2018
DOI: 10.1111/ejh.13072
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab maintenance after salvage autologous stem cell transplantation results in long‐term remission in multiple relapsed primary CNS lymphoma

Abstract: Recurrence of primary central nervous system lymphoma (PCNSL) after high-dose chemotherapy with autologous stem cell transplantation (ASCT) usually has a poor overall prognosis with limited treatment options. Data on repeated ASCT are sparse. Checkpoint inhibitor maintenance therapy has also not been reported in PCNSL. Here, we report the first documented case of a successful third ASCT in second relapse of PCNSL. Whole-exome sequencing identified a hypermutated tumor genotype. Additionally, immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Overall, 32 patients underwent HDC-ASCT, 56.4% had CR, the mPFS was 12.4 months, and the 2-year OS rate was 56.4%. A second relapse of PCNSL results in a poor prognosis; nevertheless, multiple long-term responses can be induced by repeated HD-MTX-based chemotherapy followed by HDC-ASCT in patients with eligible MTX-sensitive PCNSL ( 90 ). HDC-ASCT is also feasible and effective in elderly patients; a retrospective multicenter study by Schorb E et al.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 32 patients underwent HDC-ASCT, 56.4% had CR, the mPFS was 12.4 months, and the 2-year OS rate was 56.4%. A second relapse of PCNSL results in a poor prognosis; nevertheless, multiple long-term responses can be induced by repeated HD-MTX-based chemotherapy followed by HDC-ASCT in patients with eligible MTX-sensitive PCNSL ( 90 ). HDC-ASCT is also feasible and effective in elderly patients; a retrospective multicenter study by Schorb E et al.…”
Section: Treatmentmentioning
confidence: 99%
“…Terziev et al. ( 90 ) reported a case of PCNSL patients who achieved CR after a second relapse with nivolumab as maintenance therapy. The patient remained in remission for > 2 years and was in a good clinical state.…”
Section: Treatmentmentioning
confidence: 99%
“…The monoclonal antibodies against programmed death 1 (PD-1), also known as cluster of differentiation (CD) 279, and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4; also known as CD152), suppress T-cell receptor (TCR) responses of NHLs 711 . In particular, PD-1 blockade with nivolumab is effective in relapse and/or refractory PCNSLs 12,13 . Recent studies have shown that the signal transducer and activator of transcription 3 (STAT3) inhibitors abrogate the expression of PD-1 ligand 1 (PD-L1; also known as CD274), and PD-1 ligand 2 (PD-L2; also known as PDCD1LG2 or CD273) on a lymphoma cell line, HKBML, in addition to an adult T-cell leukemia-lymphoma cell line, ATL-T, and a splenic lymphoma with villous lymphocyte cell line, SLVL 14 .…”
Section: Introductionmentioning
confidence: 99%
“…More work is required to fully evaluate the mechanism for this combined activity, as the relief from immunosuppression could be important at priming or effector stages, or both. No specific agents for Treg depletion are in routine clinical use, but checkpoint inhibitors, which can alter Treg activity, are showing efficacy in the clinic [36,37]. Our own findings indicate that anti-CTLA-4 can be effectively combined with an α-GalCer-adjuvanted cellular vaccine in an orthotopic model of glioblastoma [38]; although not tested here, it is conceivable that checkpoint blockade could also be combined with vaccination to enhance efficacy in this CNS lymphoma model.…”
Section: Discussionmentioning
confidence: 77%